Udział w zgromadzeniu spółki kapitałowej za pomocą środków komunikacji elektronicznej po zmianach Kodeksu spółek handlowych dokonanych w ramach tzw. tarczy antykryzysowej - Leśniak, Marek (Wydawnictwo C.H. Beck, 2020)
The purpose of this article is to present chosen legal repercussions of legislative changes resulting from the act of 31.3.2020 on the amendment of the act on special solutions connected with prevention, counteracting and fighting COVID-19, other infectious diseases and crisis situations caused by them and certain other acts regarding the issue of participation in a meeting of a private limited company by means of electronic communication. The new regulation facilitates holding meetings of private limited companies using electronic means of communication, without removing the possibility of holding meetings in the „traditional” form in a specific place. The decision on this matter belongs to the person convening the meeting. The attempt by the legislator to define participation in the meeting of a private limited company using means of electronic communication more broadly defines the minimum segment of corporate rights that a participant in the meeting may perform than the previous regulation. It seems that the amendment will make remote assemblies of private limited companies more popular and secure, which in turn will improve the economic situation of companies, their shareholders and the economic environment.
Keywords: remote meetings of private limited companies; electronic means of communication